2021
DOI: 10.3390/jcm10215194
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Adipokines and Cardiovascular Ultrasound Parameters in Metabolic-Dysfunction-Associated Fatty Liver Disease

Abstract: (1) Background: The role of adipokines such as adiponectin and visfatin in metabolic-dysfunction-associated fatty liver disease (MAFLD) and cardiovascular disease remains unclear. Therefore, we aim to assess serum adiponectin and visfatin levels in MAFLD patients and associated cardiovascular parameters. (2) Methods: A cross-sectional study involving 80 participants (40 MAFLD patients, 40 controls), recruited between January and September 2020, was conducted, using both hepatic ultrasonography and SteatoTestTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Moreover, patients with NAFLD often have dyslipidemia, which is atherogenic in nature and is defined by elevated serum triglyceride levels and reduced high density lipoproteins cholesterol (HDL-C) levels [ 18 , 19 , 20 ]. Hence, NAFLD patients present an increased CV risk [ 21 , 22 , 23 ]. The atherogenic index of plasma (AIP), a novel quantitative index utilized to assess lipid levels, is a strong marker of dyslipidemia [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with NAFLD often have dyslipidemia, which is atherogenic in nature and is defined by elevated serum triglyceride levels and reduced high density lipoproteins cholesterol (HDL-C) levels [ 18 , 19 , 20 ]. Hence, NAFLD patients present an increased CV risk [ 21 , 22 , 23 ]. The atherogenic index of plasma (AIP), a novel quantitative index utilized to assess lipid levels, is a strong marker of dyslipidemia [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elevated lipid levels have been shown to be associated with atherosclerotic disease and coronary artery disease (40). However, Ismaiel et al showed no significant association between serum adiponectin and enadiponectin levels in patients with MAFLD and controls; although E/A was significantly associated with adiponectin in univariate analysis, this association weakened after multivariable linear regression (35). Considering the effects of adiponectin and enadiponectin on CVD, further studies are needed to confirm their effects on cardiovascular risk in patients with MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The increased morbidity and all-cause mortality could be attributed to several pathogenic factors, including hormones, nutrition, toxicity of intestinal disorders, insulin resistance, fat, liver inflammation, and gene functions (32-34). Adipose tissue is a highly active endocrine tissue that produces peptide adipocytokines with autocrine, paracrine, and endocrine functions, such as adiponectin and endolipins (35). Adiponectin is the most abundant peptide secreted by adipocytes; it has been found to be secreted by other cells besides endothelial cells, including bone and cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment process, hepatic steatosis and echocardiographic assessment, as well as the laboratory tests were previously described in details [ 30 , 31 ]. In summary, we performed a cross-sectional observational study, enrolling participants using non-probability consecutive sampling between January 2020 – September 2020.…”
Section: Methodsmentioning
confidence: 99%